The Digital Double Bind - Zayani, Mohamed; Khalil, Joe F. (Oxford University Press, 2025)
The Middle East’s digital turn has renewed hopes of socioeconomic development and political change across the region. It has also engendered stark contradictions and accentuated existing tensions. The resulting disjunctures are ensnaring the region in a digital double bind: the same conditions that drive the immersion of the state, market, and public in the digital also inhibit change and perpetuate stasis. Grounded in local research and anchored in rich case studies, The Digital Double Bind critically engages with the question of technology and change beyond binary formulations and familiar trajectories of the network society. It offers a pathbreaking analysis of how the Global South negotiates its relation to the digital.